2002
DOI: 10.1016/s0005-1098(02)00004-3
|View full text |Cite
|
Sign up to set email alerts
|

Explicit sub-optimal linear quadratic regulation with state and input constraints

Abstract: Optimal feedback solutions to the in nite horizon LQR problem with state and input constraints based on receding horizon real-time quadratic programming are well known. In this paper we develop an explicit solution to the same problem, eliminating the need for realtime optimization. A suboptimal strategy, based on a suboptimal choice of a nite horizon and imposing additional limitations on the allowed switching between active constraint sets on the horizon, is suggested in order to address the computer memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 25 publications
0
51
0
Order By: Relevance
“…An algorithm to solve the mp-QP is also provided, however, a more efficient algorithm is developed in (Tøndel et al, 2001). An alternative solution strategy is given in (Johansen et al, 2000), where pre-determination of a small set of sampling instants where the active set is allowed to change gives a suboptimal solution. Sub-optimality of mp-QP is also introduced in (Bemporad and Filippi, Conditionally accepted for publication with minor revisions) by adding small slacks to the optimality conditions, and in (Johansen and Grancharova, 2002), by imposing an orthogonal structure to the state space partitioning.…”
Section: Introductionmentioning
confidence: 99%
“…An algorithm to solve the mp-QP is also provided, however, a more efficient algorithm is developed in (Tøndel et al, 2001). An alternative solution strategy is given in (Johansen et al, 2000), where pre-determination of a small set of sampling instants where the active set is allowed to change gives a suboptimal solution. Sub-optimality of mp-QP is also introduced in (Bemporad and Filippi, Conditionally accepted for publication with minor revisions) by adding small slacks to the optimality conditions, and in (Johansen and Grancharova, 2002), by imposing an orthogonal structure to the state space partitioning.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the solution (the control input) has an explicit representation as a piecewise linear (PWL) state feedback on a polyhedral partition of the state space, see also [2,8,11,12], and they develop an mp-QP algorithm to compute this function.…”
Section: Introductionmentioning
confidence: 99%
“…In [1] it was recognized that the constrained linear MPC problem is a multi-parametric quadratic program (mp-QP), when the state is viewed as a parameter to the problem. It was shown that the solution (the control input) has an explicit representation as a piecewise linear (PWL) state feedback on a polyhedral partition of the state space, see also [2,8,14,15], and they develop an mp-QP algorithm to compute a representation of this function. Some of these approaches have been further extended to ensure robustness of the explicit MPC controllers against disturbances [3,11,13].…”
Section: Introductionmentioning
confidence: 99%